Ecotoxicological assessment of Ti3C2Tx (MXene) using a zebrafish embryo model. Issue 4 (20th March 2018) - Nasrallah, Gheyath K.; Al-Asmakh, Maha; Rasool, Kashif; Mahmoud, Khaled A.
Abstract : We studied the biocompatibility of Ti3 C2 T x MXene sheets by analyzing their potential toxicity in vivo and their potential risks on marine biota and ecosystems using a zebrafish embryo model. Abstract : The recent application of 2D Ti3 C2 T x (MXene) nanomaterials as adsorbents and membranes for water treatment as well as for biomedical applications is attracting a growing interest. However, the environmental impact of MXene nanomaterials, especially their potential risks on aquatic biota and ecosystems of the aquatic environment, has never been explored. Herein, we have studied the biocompatibility of Ti3 C2 T x by analyzing its potential toxicity in vivo using a zebrafish embryo model. Ti3 C2 T x morphology, surface charge, and stability were characterized by SEM, TEM, and X-ray diffraction spectroscopy. The aggregation patterns of Ti3 C2 T x suspensions in seawater were investigated. The ICP-MS results showed that the zebrafish embryos can uptake Ti3 C2 T x in a dose dependent manner. The acute toxicity of attached/absorbed Ti3 C2 T x was tested at concentrations of 25, 50, 100 and 200 μg mL −1 . According to the 96-hour sigmoidal mortality curve, the LC50 of Ti3 C2 T x was calculated to be 257.46 μg mL −1 and the highest NOEC (<20% mortality) was 50 μg mL −1 . The LOEC (≥20% mortality) of Ti3 C2 T x was detected to be 100 μg mL −1, as this concentration showed a slight increase in mortality (21%). However, no significant teratogenic effects were observed on zebrafish embryos at 100 μg mL −1 . This nontoxicity was confirmed by locomotion and neurotoxicity assays, as 50 μg mL −1 of Ti3 C2 T x showed no harmful effects on neuromuscular activities. In conclusion, because the LC50 of Ti3 C2 T x was greater than 100 μg mL −1, it can be classified as within the "practically nontoxic" group according to the Acute Toxicity Rating Scale by the Fish and Wildlife Service (FWS); thus, we suggest the safe use and discharge of Ti3 C2 T x MXene in the aquatic ecosystem at concentrations below 100 μg mL −1 .